ANALISIS SCP PADA INDUSTRI PROPERTI DI INDONESIA - Nurhayati ,; Husna Leila Yusran (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
The purpose of this study is to determine how the structure, market concentration and efficiency of the property industry in Indonesia. The analysis technique used in this research is Concentration Ratio (CR10), Herfindahl Index-Hirschman (IHH) and Data Envelopment Analysis (DEA). Total revenue of the Indonesia property industry from 2010-2014 is used to calculate Concentration Ratio (CR10) and Herfindahl Index-Hirschman (IHH), while the Data Envelopment Analysis (DEA) is input and output, the input consists of total assets, debt, and equity, the output consists of total sales and profits. Based on the analysis the results of Concentration Ratio (CR10) is quite high, ranging from 74.65% - 77.16%, the market structure in the property industry classified within a tight oligopoly. Based on IHH has a range of numbers from 0.1013 to 0.56667, which means competition Indonesian property industry and the competitive nature of high concentration. Results DEA in 2010-2010 there are 4-8 efficient companies. As a result of which are oligopolistic and competitive, the companies in the property industry are doing a lot in marketing strategy as well as to achieve efficient companies should refer to the property industry has already reached the maximum efficient rate.